The Canonical Robot Command Language (CRCL). Issue 5 (15th August 2016) - Proctor, Frederick; Balakirsky, Stephen; Kootbally, Zeid; Kramer, Thomas; Schlenoff, Craig; Shackleford, William
Abstract : Purpose: This paper aims to describe an information model, the Canonical Robot Command Language (CRCL), which provides a high-level description of robot tasks and associated control and status information. Design/methodology/approach: A common representation of tasks was used that is understood by all of the resources required for the job: robots, tooling, sensors and people. Findings: Using CRCL, a manufacturer can quickly develop robotic applications that meet customer demands for short turnaround, enable portability across a range of vendor equipment and maintain investments in application development through reuse. Originality/value: Industrial robots can perform motion with sub-millimeter repeatability when programmed using the teach-and-playback method. While effective, this method requires significant up-front time, tying up the robot and a person during the teaching phase.